(untitled) (Research, Society and Development, 2023)
Albumin is the most important plasma expander in the bloodstream. In the form of medication, it must be prescribed after a thorough evaluation of the patients, basing its use according to the literature, as it has contraindications, such as bleeding in post-surgical patients, in addition to being a high-cost medication. Thus, the objective of this work was to carry out a survey of the therapeutic indications contained in the prescriptions of human albumin (HA) 20% of a Teaching Hospital in the city of Recife, Pernambuco, Brazil, in order to assess whether such indications have scientific basis, in addition to a survey of the costs related to the acquisition of this drug should be carried out. A cross-sectional, retrospective study was carried out, based on the analysis of prescriptions prescribed to patients, from May 2015 to May 2017. The therapeutic indications found were: relief paracentesis (29%), hepatorenal syndrome (HRS) (22,9%), hypovolemia (20.6%), septic shock (8.7%), spontaneous bacterial peritonitis (SBP) (6.4%), hypoalbuminemia (6.1%), ascites (4.1%), neoplasia (1.2%) and hepatic encephalopathy (HE) (0.6%). After a literature review, HA 20% has scientific support for the treatment of paracentesis, SHR and PBE, which corresponds to 63.1% of prescriptions and has no scientific support for the treatment of hypovolemia, septic shock, hypoalbuminemia, cancer and HE (36.9%), which can be replaced by other plasma expanders. Thus, the importance of basing the prescription of 20% HA according to the literature is highlighted, always aiming at the rational use of medicines.